Washeteria closures, infectious disease and community health in rural Alaska: a review of clinical data in Kivalina, Alaska - Thomas, Timothy K. (Co-Action Publishing, 2013)
BACKGROUND: Kivalina is a northwest Alaska barrier island village of 400 people vulnerable to storm surges exacerbated recently by delayed winter sea and shore ice formation. The village has no in-home piped water or sewage; the “washeteria” is the only structure providing public showers, laundry facilities and flush toilets. In October 2004, a storm damaged the washeteria septic system resulting in prolonged facility closures. We assessed rates of gastrointestinal, respiratory and skin infections potentially impacted by prolonged washeteria closures. METHODS: We obtained washeteria closure dates from 2003 to July 2009 and defined >7 day closure as prolonged. We received de-identified data on all Kivalina clinic visits from 2003 to 2009 and selected visits with ICD-9 diagnosis codes for respiratory, skin, or gastrointestinal infection; subsequent same patient/same illness-category visits within 14 days were excluded. We compared annual visit rates, for all ages combined, before (2003–2004) and after (2005–2009) the “2004” storm. RESULTS: The washeteria had prolonged closures for 34 days (4.7%) in the 2 years 2003–2004 and 864 days (51.7%) between January 2005 and July 2009. Closures ranged from 8 to 248 days. Respiratory infection rates declined significantly from 1.32 visits/person/year in the 2003–2004 period to 0.99 visits/person/year in the 2005–2009 period. There was a significant increase in skin infection rates after 2004, peaking at 0.28 visits/person/year in 2007 and then declining significantly to 0.15 visits/person/year in 2009. Gastrointestinal infection rates remained stable and low throughout (average: 0.05 visits/person/year). No temporal association was observed between respiratory, gastrointestinal or skin infection rates and prolonged washeteria closures. CONCLUSION: The Kivalina washeteria was closed frequently and for extended periods between 2005 and 2009. Initial closures possibly resulted in increased skin infection rates. No increase in respiratory or gastrointestinal infections was noted. Evaluation of community adaptations to closures and other factors (e.g. childhood pneumococcal vaccination) would expand understanding of these findings.